TRANSFORMASI DIGITAL INDUSTRI HALAL: IMPLIKASI TERHADAP PENGEMBANGAN KOMPETENSI DAN KINERJA SUMBER DAYA MANUSIA - Ali Achmad Muhajir; Ahmad Munajim; Cory Vidiati (Jurnal Riset Multidisiplin Edukasi, 2026)
Digital transformation has become a strategic driver of change across various industrial sectors, including the halal industry. The adoption of digital technologies, such as artificial intelligence (AI), the Internet of Things (IoT), big data, cloud computing, and digital platforms, has not only improved operational efficiency but also reshaped the competency requirements of human resources (HR). This study aims to analyze the influence of digital transformation on HR competency development, identify its implications for HR performance, and formulate adaptive competency development strategies to support digital transformation in the halal industry. The study employed a qualitative method using a library research approach by examining scientific articles, academic books, institutional reports, government documents, and regulations related to digital transformation and the halal industry. Data were analyzed using content analysis through data reduction, thematic categorization, and literature synthesis. The findings indicate that digital transformation acts as a driving force in enhancing digital competencies, halal competencies, and soft skills, which subsequently improve productivity, operational efficiency, service quality, data-driven decision-making, and halal product innovation. Nevertheless, the implementation of digital transformation continues to face several challenges, including digital competency gaps, resistance to change, limited training opportunities, data security issues, and unequal technology adoption among halal industry stakeholders. Therefore, integrated human resource development strategies through digital upskilling, reskilling, multi-stakeholder collaboration, and the strengthening of a digital organizational culture are essential to ensure that digital transformation enhances the sustainable competitiveness of the halal industry.